2002
DOI: 10.1002/jnr.10195
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐dependent hypoxic tolerance mediated via gender‐specific mechanisms

Abstract: Primary hypoxic tolerance and preconditioning are gender dependent and modulated in females during the estrus cycle. The underlying mechanisms, however, remain to be determined. mRNA of estrogen receptor-alpha (EAR), progesterone receptor (PR), and adenosine receptor subtypes A1 and A3 (A1R and A3R) were investigated with reverse transcriptase-PCR in hippocampi from control male and female mice and animals treated in vivo with a single i.p. injection of 20 mg/kg body weight 3-nitropropionate (3NP) 1 or 24 hr p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Variants in adenosine receptor genes including ADORA3 and ADORA1 may predict cardiac response to ischemia or injury 32. Upregulation of adenosine A3 receptors mRNA upon preconditioning is sex specific and depends on a woman's menstrual cycle 33. In this study, the gene region of A1 receptors was alike in both women and men.…”
Section: Discussionmentioning
confidence: 64%
“…Variants in adenosine receptor genes including ADORA3 and ADORA1 may predict cardiac response to ischemia or injury 32. Upregulation of adenosine A3 receptors mRNA upon preconditioning is sex specific and depends on a woman's menstrual cycle 33. In this study, the gene region of A1 receptors was alike in both women and men.…”
Section: Discussionmentioning
confidence: 64%
“…Sex-specific isoflurane preconditioning in ischemic brain H Kitano et al tolerance of hippocampal slices from mice chemically preconditioned with 3-nitro-propionate concluded that hypoxic tolerance and preconditioning are gender-dependent and modulated during the estrous cycle by gender-specific mechanisms (Kasischke et al, 1999;Von Arnim et al, 2002). These observations challenge the assumption that the general response to preconditioning is similar in brains of either sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not address this controversy but used fundamental paradigms to test estradiol signaling and IsoPC mechanisms, as little work has been done evaluating the role of ERs in anesthetic or other forms of preconditioning in the ischemic female brain. For example, in a model of hypoxic tolerance using mice preconditioned with 3-nitro-propionate, Von Arnim et al (2002) have observed that ER α mRNA levels were found to be similar in males and females and were unaltered by 3-nitropropionate preconditioning. Interestingly, increased protein levels of ER α but not ER β in the cortex were observed 24 h after hypoxic preconditioning in neonatal rats (Cimarosti et al , 2005).…”
Section: Discussionmentioning
confidence: 99%